Learning strategies implemented by the students of advanced intensive english I courses for improving oral discourse in the Bachelor of Arts in English teaching, Department of Foreign Languages, University of El Salvador, year 2014 - Gómez Vásquez, Karen Cecilia
There are many learning strategies some, more successful than others when they are applied in a correct way. “Strategies are most successful when they are implemented in a system that encourages collaboration among staff and students, and in which each is a part of a well-planned whole system” (Johns Hopkins, 2000). Additionally, Learning strategies have become an effective instrument in the field of education because students can make use of several strategies in order to enhance their English level in terms of communication. To communicate in a meaningful way, it is important to express ideas inside and outside the classroom; it is part of the development and improvement of speaking.